Microplastics impair the feeding performance of a Mediterranean habitat-forming coral. (March 2020) - Savinelli, Beatrice; Vega Fernández, Tomás; Galasso, Nicola Maria; D'Anna, Giovanni; Pipitone, Carlo; Prada, Fiorella; Zenone, Arturo; Badalamenti, Fabio; Musco, Luigi
Abstract: The impact of plastic debris, and in particular of microplastics (here referred as particles smaller than 5 mm) on aquatic environments has now become a topic of raising concern. Microplastics are particularly abundant in the Mediterranean Sea, potentially exerting substantial pressures on marine organisms at different levels of organization. Ingestion of microplastics has been observed in a large number of marine species. The aim of this work is to test if microplastics produce a feeding impairment in Astroides calycularis, a shallow water, habitat-forming coral endemic to the Mediterranean Sea. Our findings suggest a lack of any avoidance mechanism allowing the polyps to discern between food items and microplastics when occurring simultaneously. Moreover, polyps spend a considerable amount of time on handling microplastic particles. As a consequence, microplastics impair the feeding efficiency in A. calycularis, since polyps may not be fully able to profit from the drifting plankton aggregations. Therefore, we suggest that microplastics can cause a reduction of fitness in A. calycularis, and presumably also in other species characterized by suspension feeding strategy. Highlights: The coral Astroides calycularis captures, ingests, and egests microplastics. Presence of food stimulates microplastics ingestion by the coral. Occurrence of microplastics extends handling time in the coral. Microplastics impair food intake in the coral. Microplastics are expected to undermine fitness in the coral.